Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1590/s0104-11692010000500018
|View full text |Cite
|
Sign up to set email alerts
|

The Educative Game as a Sensitization Strategy for the Collection of Data with Adolescents

Abstract: The aim of this study was to understand and analyze the potential of a game as a sensitization strategy for the performance of focal groups with adolescents in investigations into values.Twenty nine groups were realized in 10 social institutions of the municipality of Santo André. The sample was composed of 209 adolescents of 15 to 19 years of age. The results indicated that the majority expressed themselves without difficulties, discussing each of the valorative expressions drawn during the game with resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 8 publications
0
14
0
5
Order By: Relevance
“…Conversely, two studies comparing these two methods found that the ‘pen and paper’ method elicited higher levels of disclosure when exploring sensitive topics [43,44]. …”
Section: Resultsmentioning
confidence: 99%
“…Conversely, two studies comparing these two methods found that the ‘pen and paper’ method elicited higher levels of disclosure when exploring sensitive topics [43,44]. …”
Section: Resultsmentioning
confidence: 99%
“…[4][5] The use of games is an instrument of the educational process in health that favors participation, debates and exchange of experiences, From a critical perspective in relation to traditional education. 6 The use of educational games for adolescents has shown that playful and participatory work fosters arguments, reflections and collective construction of knowledge among them. [7][8] Therefore, it becomes relevant to unleash efforts for the production and validation of educational technologies directed to this public.…”
Section: Introductionmentioning
confidence: 99%
“…The game also encourages learning exposed in situations and in the context in which it is involved [16].…”
Section: Discussionmentioning
confidence: 99%
“…Dialogue is critical here, to allow exchange of information and consequently exchange of knowledge [16].…”
Section: Discussionmentioning
confidence: 99%